Interactive effects of principal's leadership styles and quality assurance initiative on teacher commitment in the islamic private secondary schools in southern Thailand - Hatyida-Oh, Nasruddeen (Kulliyyah of Education, International Islamic University Malaysia, 2015)
The main purpose of the study is to investigate the interactive effects of principal's leadership styles (INTELS) Principal Transformational Leadership Style (PTLS) and Principal Strategic Leadership Style (PSLS)] and Quality Assurance Initiatives (QAI) on Teacher Commitment (TC) in the Islamic Private Secondary Schools in Southern Thailand. The study also attempted to measure the strength of mediating variable, quality assurance initiatives on the relationship between principal leadership styles and teacher commitments in the schools concerned. As the study was a quantitative in nature, the sample size was 553 (95% confidence interval and ± 4%) represented by Muslim teachers from the Islamic Private Secondary Schools in three provinces (Pattani, Yala and Narathiwat), in Southern Thailand. This study utilized the two-steps analysis of Structural Equation Modeling (SEM) techniques. The first four research questions were addressed by analyzing all four measurement models and the study found that the proposed constructs namely PTLS, PSLS, QAI and TC items were loaded significantly into their respective constructs. In the next step of SEM technique, the fifth and sixth research questions were addressed by evaluating and re-specifying the hypothesized model. The results indicated that the re-specified model was very encouraging with the values of X2/df = 2.684, TLI = 893, CFI = .901, GFI = .850, IFI = .90 and RMSEA = .054. From the re-specified model of the study, it was found that PTLS and PSLS factors influenced TC. The model also revealed that only two factors of PTLS, namely visionary (V) and individual orientation (IO) directly influenced TC and four factors of PSLS, namely wisdom (WD), strategic orientation (SO), strategic competence (SC) and strategic translation (ST) directly influenced TC. As for the research questions number 7, 8 and 9, the study proved that the mediating variable, QAI did not significantly influence the relationships between PTLS and PSLS with TC. Finally, the study managed to prove that the hypothesized model fit to the data and hence represent the model of the study. Some of the practical implications are that some aspects of the PTLS and PSLS are deemed important to the principals of the Islamic Private Secondary Schools in Southern Thailand and to the policy makers concerned in their strategies to improve the survivability of the Islamic Private Secondary Schools in Southern Thailand. Theoretically, the study managed to contribute to the literature in terms of the need of the principals of the Islamic Private Secondary Schools in Southern Thailand to practice some factors of PTLS and PSLS for the betterment of the schools concerned. The novelty of the study indeed related to the modern strategies that can be used effectively in improving the Islamic Private Secondary Schools in southern Thailand particularly the PTLS and PSLS.